Analysis of patterns in the concentrations of atmospheric greenhouse gases measured in two typical urban clusters in China. (January 2018) - Liu, Lixin; Tans, Pieter P.; Xia, Lingjun; Zhou, Lingxi; Zhang, Fang
Abstract: China is the largest emitter of greenhouse gases, and urban clusters play an essential role in China's carbon emissions because of the country's unbalanced economic development. In this paper, the discrete air sample measurements of atmospheric CO2, CH4, and CO during the period between 2007 and 2013 from Shangdianzi (SDZ) station in Jing-Jin-Ji (JJJ) region and Linan (LAN) station in Yangtze River Delta (YRD) region, respectively, are presented and characterized. By backward trajectory cluster analysis, the low background CO2 mole fraction and similar long-term trends with Waliguan global station (WLG) were observed at SDZ because most of the air masses originate mostly from remote clean terrestrial areas in the north with limited information of anthropogenic emissions. But the background CH4 and CO are influenced mainly by ruminants and rice field emission from the surrounding regions and urban cluster emission in the JJJ region, which lead to the higher CH4 and CO in summer at SDZ. Whereas, the CO2, CH4 and CO background values observed at LAN are higher by the combined effects of long-distance atmospheric transportation from Northern and Central China and urban clusters emission from the YRD region. The observed polluted data at SDZ and LAN are all strongly affected by regional and local anthropogenic emissions, which lead to the higher GHGs concentrations compared to the background data. However, because the air mass transportation from the north is weak in winter and no winter heating is required and vegetation photosynthesis is still stronger in the south of China, the CO2 concentration at LAN is lower than that at SDZ in autumn and winter. The polluted CO value at SDZ is found considerably higher than that at LAN, especially in spring and winter. By analyzing the correlations of observed regional enhanced values of CO2, CH4 and CO at the two stations, we find the significant correlation between them, which means they may share the common-source of anthropogenic emissions from the regional fossil fuel and biomass burning in cold season. Moreover, the high coal-consumption proportion with the low CO2 emissions factors, and much biomass burning with low combustion efficiency in JJJ region lead to the higher slope values of △CO2 and △CO in spring and winter at SDZ and considerably higher than that at LAN. The results can provide a further understanding of regional/local features of atmospheric GHGs under the influence of human activities in the urban clusters in China. Highlights: Background values at SDZ were mainly influenced by long-distance transportation. Background values at LAN are obviously higher than other stations. Polluted data at SDZ and LAN are strongly affected by regional and local emissions. Polluted CO2 concentration at LAN is lower than that at SDZ in autumn and winter. Coal and biomass burning in JJJ lead to the higher ratios of △CO2 -△CO at SDZ.